PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN METODE IMPROVE BERBASIS PEMECAHAN MASALAH MODEL POLYA SUB POKOK BAHASAN LINGKARAN KELAS VIII SMP SEMESTER GENAP TAHUN AJARAN 2013/2014 - Sari, Erna Yunita; Sunardi, S; Susanto, S (KadikmA, 2015)
Abstract: The goal of this research aims to know the process and the result of the development of Mathematics Learning Instruments by using IMPROVE method based on Polyaâs problem solving model in sub topic of circle at the second semester of the eighth grade students of junior high school in the 2013/2014 Academic Year. Learning instruments development model refers to four D models. The products of this research are lesson plan, student book, worksheet, and evaluation test. The products refer to the phases of IMPROVE method based on Polyaâs problem solving model. The subject of the research is students of grade VIII D SMPN 14 Jember. The data collection methods used in this research are the validation, test, observation, and questionnaire. Based on the validation process try out of learning instruments, it can be concluded that the learning instrumets have satisfied criteria the validity, practicality, and effectiveness. Key words: IMPROVE Method, Polyaâs problem solving model, circle